Proposed An Intelligent System for Electricity Theft Detector at Smart City Scenarios - Syifaul Fuada (Institute of Advanced Engineering and Science, 2016)
This is a conceptual proposal which is aimed at describing an intelligent security system to early detect cases of electricity theft which is claimed effective to cope with ICT based cases of electrecity theft. The method employed in the detector is computation system, which is the computation of phase differences (Φ), current voltage in real time and losses detection of electrical power grid by 220V. The losses calculation employs Kirchoff’s law I which is Kirchoff’s current law. The current sensors are put on the output distribution transformer and on customer’s APP connection. The working principles are (1) reading output current and phase differences at the load point (of the customer’s) in the distribution transformer using the current sensor, (2) comparing the output current (Io) with the sum of certain variables on consumers to be discussed in this paper. (3) Knowing the data of electric current usage by recording data of losses in real time and by sending them to teh control center monitoring in real time.